2014
DOI: 10.3126/njst.v14i2.10428
|View full text |Cite
|
Sign up to set email alerts
|

Bacteriological Study of Wound Infection and Antibiotic Susceptibility Pattern of the Isolates

Abstract: Wound infections result in sepsis, limb loss, long hospital stays, higher costs, and are responsible for significant human mortality and morbidity worldwide. The present study was conducted to isolate and identify the causative organisms of wound infection, to determine the antibiotic susceptibility pattern of the isolates and to study the risk factors for wound infection. The study was conducted for six months in which pus specimens collected from 244 patients were processed to investigate etiological agents … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 26 publications
2
6
1
Order By: Relevance
“…The high prevalence of Gram-positive organism might be due to the presence of Gram-positive bacteria as a normal flora of the human body. The result was found to be similar to the research conducted by KC et al [35]; Devi et al [37] and Pant et al [36]. The result was found contrast to the study conducted by Patil et al (2019)78% gram negative and 22% Gram-positive bacteria [34].…”
Section: Discussionsupporting
confidence: 66%
See 1 more Smart Citation
“…The high prevalence of Gram-positive organism might be due to the presence of Gram-positive bacteria as a normal flora of the human body. The result was found to be similar to the research conducted by KC et al [35]; Devi et al [37] and Pant et al [36]. The result was found contrast to the study conducted by Patil et al (2019)78% gram negative and 22% Gram-positive bacteria [34].…”
Section: Discussionsupporting
confidence: 66%
“…High prevalence of growth in OPD might be due to increase in community acquired infection. Higher positive growth in OPD was also found in the study carried by KC et al [35] and found contrary to the study carried out by Pant et al, where they found 63.1% from IPD and 56.2% from OPD [36].…”
Section: Discussioncontrasting
confidence: 56%
“…We found that the most common bacterial isolates were E. coli, followed by S. aureus. The most predominant bacteria were E. coli supported by (Gautam et al, 2013;KC et al, 2013). The most predominance of S. aureus and the second most predominant bacteria is E. coli in a wound is supported by many studies (Karki 2012;Shrestha et al,2009).…”
Section: Resultsmentioning
confidence: 76%
“…15 Because colistin resistance has already been reported in some parts of the world, it may be expected in this region too though not reported yet. 4,[9][10][11][12]15 Combination of colistin with meropenem is shown ineffective in preventing emergence of resistance to colistin in a study. So judicious use of this valuable antibiotic seems to be the way to preserve sensitivity of the highly resistant organisms.…”
Section: Discussionmentioning
confidence: 98%